Realizing Smart City Through Jababeka Smart Township Super Apps - Yunita Ismail Masjud; Adhi Setyo Santoso; Chong Mi An (President University, 2022)
– The community service activity, which is a combination of three President University flagship researches about the creation of a Smart Ecosystem that will be outlined in the Jababeka Smart Township application, allows students and the community to work together to build a Smart city in the Jababeka area. The goal of this community service project is to create a smart city that involves everyone. The strategy employed is direct community implementation by involving President University instructors and students. According to the findings, Jababeka Smart Township Super Apps invites the community and students to participate in and contribute to this application. According to waste management studies, there is a need for timely and accurate information about the presence of garbage and the availability of waste processing facilities. Waste processing facilities were discovered as a result of waste management research. According to the findings, Jababeka Smart Township Super Apps invites the community and students to participate in and contribute to this application. According to waste management studies, there is a need for timely and accurate information about the presence of garbage and the availability of waste processing facilities. Garbage processing and waste management facilities can be visited by the general public, according to waste management studies. The trash management app on display at Jababeka Smart Township Super Apps will assist the community in garbage management while also allowing them to participate in waste management. President University's flagship tourism development research will provide information on tourist locations and all accessible tourist facilities, as well as accessibility to these tourist attractions. Furthermore, the need for information on the tourism industry might lead to the formation of tourism-related start-ups.